Gypsy, Roma and Traveller access to and engagement with health services: a systematic review. (16th January 2018) - McFadden, Alison; Siebelt, Lindsay; Gavine, Anna; Atkin, Karl; Bell, Kerry; Innes, Nicola; Jones, Helen; Jackson, Cath; Haggi, Haggi; MacGillivray, Steve
Abstract: Background: Gypsy, Roma and Traveller people represent the most disadvantaged minority groups in Europe, having the poorest health outcomes. This systematic review addressed the question of how Gypsy, Roma and Traveller people access healthcare and what are the best ways to enhance their engagement with health services. Methods: Searches were conducted in 21 electronic databases complemented by a focussed Google search. Studies were included if they had sufficient focus on Gypsy, Roma or Traveller populations; reported data pertinent to healthcare service use or engagement and were published in English from 2000 to 2015. Study findings were analyzed thematically and a narrative synthesis reported. Results: Ninety-nine studies from 32 countries were included, covering a range of health services. Nearly one-half of the presented findings related to primary healthcare services. Reported barriers to health service usage related to organisation of health systems, discrimination, culture and language, health literacy, service-user attributes and economic barriers. Promising engagement strategies included specialist roles, outreach services, dedicated services, raising health awareness, handheld records, training for staff and collaborative working. Conclusion: This review provides evidence that Gypsy, Roma and Traveller populations across Europe struggle to exercise their right to healthcare on account of multiple barriers; and related to other determinants of disadvantage such as low literacy levels and experiences of discrimination. Some promising strategies to overcome barriers were reported but the evidence is weak; therefore, rigorous evaluations of interventions to improve access to and engagement with health services for Gypsy, Roma and Traveller people are needed.